Genome-Wide Analyses of Prognostic and Therapeutic Alternative Splicing Signatures in Bladder Urothelial Carcinoma - Fan, Zhongru; Zhang, Zhe; Piao, Chiyuan; Liu, Zhuona; Wang, Zeshu; Kong, Chuize (Frontiers in Oncology, 2021)
Background: Alternative splicing (AS) is an indispensable genome modification link of posttranscription for producing mature mRNA, whose defects may give rise to many cancers. This study is designed to thoroughly analysis alternative splicing events in Bladder Urothelial Carcinoma (BLCA) at genome-wide level. Methods: We adopted gap analysis to screen for differential alternative splicing events with significant differences in BLCA, and Cox regression analysis to identify the prognostic signatures of BLCA. Overall survival (OS) and disease free interval (DFI) prognosis model were established. In addition, a differential alternative splicing network as well as alternative splicing clusters identified by unsupervised cluster analysis were conducted. We also speculated on the differences in sensitivity to chemotherapy and immunotherapy between patients with high or low OS risk of BLCA. Results: Extensive DASEs (296) were found to be clinically relevant in bladder urothelial carcinoma (BLCA). Then, the OS and DFI prognostic alternative splicing events were identified by Cox analysis. Meanwhile, CUGBP elav-like family member 2 (CELF2) is a hub splicing factor in alternative splicing networks. We also identified alternative splicing clusters associated with overall survival (OS) by unsupervised cluster analysis, and we predicted that the effects of cisplatin and gemcitabine chemotherapy are different between high and low risk groups for OS prognosis. Conclusion: We strengthened the recognition of differential alternative splicing network regulator mechanisms for BLCA and developed two prognostic AS signatures that can play a guiding role in cancer therapy.